A study on correlation of degree of midline shift on CT scan and Glasgow coma scale in patients of acute traumatic head injury - Ratnakar, Akhilesh (International Journal of Research in Medical Sciences, 2017)
Background:The present study is undertaken to analyses the patients of craniocerebral injury with special reference to correlation between Glasgow coma scale score and CT scan findings at the time of admission. Methods: A study was conducted on patients with acute traumatic head injury. Most common and important complication of traumatic head injury is the development of an increased intracranial pressure resulting in midline shift. The larger the amount of the midline shift on CT scan the poorer will be the outcome of traumatic head injury. Other variables such as Glasgow coma scale have been subsequently introduced to build more complex and accurate prognostic model. In Glasgow coma scale it was found that confident prediction could be made only after 24 hours. Results:Cerebral contusion was the most common CT scan finding followed by depressed fracture), subdural hematoma (15.3%) than extradural hematoma. Hemorrhagic contusion was the most common CT scan finding irrespective of GCS score. In patients with GCS 3-5 other outcome findings are extradural hematoma, subdural hematoma, & depressed fracture. In patients with GCS 6-8 other common findings are extradural hematoma, depressed fracture & hemorrhagic contusion. In patients with GCS 9-12 other common findings were hemorrhagic contusion, depressed fracture & intra cerebral hematoma. In patients with GCS 13-15 other common findings were depressed fracture, hemorrhagic contusion. Conclusion:The increased degree of midline shift in patients with head injuries by CT scan was related to the severity of head injury (GCS= 3-12) and was significantly related to poor final clinical outcome.